Graphene Oxide Sheets Decorated with Octahedral Molybdenum Cluster Complexes for Enhanced Photoinactivation of Staphylococcus aureus - Guégan, Régis; Cheng, Xiaoxue; Huang, Xiang; Němečková, Zuzana; Kubáňová, Michaela; Zelenka, Jaroslav; Ruml, Tomáš; Grasset, Fabien; Sugahara, Yoshiyuki; Lang, Kamil; Kirakci, Kaplan (Inorganic chemistry, 2023)
The emergence of multidrug-resistant microbial pathogens poses a significant threat, severely limiting the options for effective antibiotic therapy. This challenge can be overcome through the photoinactivation of pathogenic bacteria using materials generating reactive oxygen species upon exposure to visible light. These species target vital components of living cells, significantly reducing the likelihood of resistance development by the targeted pathogens. In our research, we have developed a nanocomposite material consisting of an aqueous colloidal suspension of graphene oxide sheets adorned with nanoaggregates of octahedral molybdenum cluster complexes. The negative charge of the graphene oxide and the positive charge of the nanoaggregates promoted their electrostatic interaction in aqueous medium and close cohesion between the colloids. Upon illumination with blue light, the colloidal system exerted a potent antibacterial effect against planktonic cultures of Staphylococcus aureus largely surpassing the individual contributions of the components. The underlying mechanism behind this phenomenon lies in the photoinduced electron transfer from the nanoaggregates of the cluster complexes to the graphene oxide sheets, which triggers the generation of reactive oxygen species. Thus, leveraging the unique properties of graphene oxide and light-harvesting octahedral molybdenum cluster complexes can open more effective and resilient antibacterial strategies.
Keywords: Staphylococcal Infections; molybden; Staphylococcus aureus; reaktivní formy kyslíku; Humans; Anti-Bacterial Agents; lidé; antibakteriální látky; Molybdenum; Reactive Oxygen Species; stafylokokové infekce